Bubble occurrence and landing - Wan, Junmin (Journal of Financial Stability, 2024)
First, a rational bubble with a stochastic crash is modelled under conditions of timelessness (or strictly a zero interest rate) and an infinite number of investors. The necessary and sufficient conditions for this bubble are a strictly positive bubble premium and a sufficient number of investors. Second, it is shown that a rational bubble occurs under a strictly negative interest rate. Finally, whether bubbles can be prevented or landed is discussed.